Prospects and Challenges of Zakat in the Modern Economy - Jalaluddin Rum; Wa Ode Ramla; Muh. Suwardi; Farid Rahman Hamsa; Mardan (LP2M IAIN Palopo, 2025)
This study aims to comprehensively analyze the prospects and challenges of implementing zakat as an instrument of Islamic philanthropy in the modern economic system. Using a literature review method, this article synthesizes findings from various scientific literature. The analysis shows that zakat's prospects lie in its great potential as an economic stabilizer, a tool for wealth distribution, and a driver of inclusive growth, supported by the digitalization of management (Zakat Fintech) and its application to contemporary assets (such as professional zakat and digital assets). However, the main challenges faced include harmonizing Islamic jurisprudence regulations regarding new financial instruments, increasing zakat payer compliance, issues of accountability and institutional governance, and the urgent need for measurable impact measurement. Optimizing the role of zakat requires institutional synergy, technological innovation, and policy reforms that support the transformation of zakat funds from consumptive to productive.